Corporate governance e desempenho das empresas de seguros em Portugal - Oliveira, Mafalda Alexandra Borges (2021)
The theme of Corporate Governance and business performance has been widely discussed and analyzed, but the results on this relationship are mixed. Therefore, the main issue addressed in this dissertation is whether there is a relationship between the internal mechanisms of corporate governance and the performance of companies. For this, a sample composed of the 10 largest life and non-life insurance companies, selected by the criterion of total production, in the period from 2010 to 2019. The methodology used consisted of estimating and analyzing multiple regression models of panel data with fixed effects, to verify the influence of Corporate Governance characteristics on business performance, measured by three indicators: return on assets (ROA), return on equity (ROE) and a combined ratio that measures operating profitability (RC). According to PLS (Panel Least Squares) regressions, the results provide some evidence of a relationship between the characteristics of the board of directors and governance mechanisms and the performance of insurers. The models indicate that board size and the separation of the roles of CEO and Chairman is positively related to performance. The findings show that a longer term of office of executive directors worsens the performance measured by ROE and RC. The longer term of office for non-executives seems to have a positive impact on asset profitability (ROA). A higher variable remuneration of executive directors relates positively to firm performance, while the weight of the shareholder in the board of directors was not related to performance. The independence of the board of directors and the auditing revealed a negative association with performance. Furthermore, the effects of the Portuguese economic and financial crisis (2010-2009) only impacted operating profitability.